Serum levels of trimethylamine N-oxide and kynurenine novel biomarkers are associated with adult metabolic syndrome and its components: a case-control study from the TEC cohort - Mirzababaei, Atieh; Mahmoodi, Maryam; Keshtkar, Abbasali; Ashraf, Haleh; Abaj, Faezeh; Soveid, Neda; Hajmir, Mahya Mehri; Radmehr, Mina; Khalili, Pardis; Mirzaei, Khadijeh (Frontiers in Nutrition, 2024)
Background: Epidemiologic research suggests that gut microbiota alteration (dysbiosis) may play a role in the pathogenesis of metabolic syndrome (MetS). Dysbiosis can influence Trimethylamine N-oxide (TMAO) a gut microbiota-derived metabolite, as well as kynurenine pathways (KP), which are known as a new marker for an early predictor of chronic diseases.Hence, the current study aimed to investigate the association between KYN and TMAO with MetS and its components.Methods: This case-control study was conducted on 250 adults aged 18 years or over of Tehran University of Medical Sciences (TUMS) Employee's Cohort study (TEC) in the baseline phase.Data on the dietary intakes were collected using a validated dish-based food frequency questionnaire (FFQ) and dietary intakes of nitrite and nitrate were estimated using FFQ with 144 items. MetS was defined according to the NCEP ATP criteria. Serum profiles TMAO and KYN were measured by standard protocol.The mean level of TMAO and KYN in subjects with MetS was 51.49 pg/mL and 417.56 nmol/l. High levels of TMAO (≥30.39pg/mL) with MetS were directly correlated, after adjusting for confounding factors, the odds of MetS in individuals 2.37 times increased (OR: 2.37, 95% CI:1.31-4.28, P value=0.004), also, high levels of KYN (≥297.18nmol/L) increased odds of Mets+ 1.48 times, which is statistically significant (OR: 1.48, 95% CI: 0.83-2.63, P value=0.04). High levels of TMAO compared with the reference group increased the odds of hypertriglyceridemia and low HDL in crude and adjusted models (P<0.05). Additionally, there was a statistically significant high level of KYN increased odds of abdominal obesity (P<0.05).Our study revealed a positive association between serum TMAO and KYN levels and MetS and some of its components. For underlying mechanisms and possible clinical implications of the differences. Prospective studies in healthy individuals are necessary